Performativity, Cybernetic Subjectivities and Politics of Psychology: Devices for Other Agencies - Calquin-Donoso, C (Springer International Publishing, 2022)
The purpose of the article is to problematize the way in which social psychology has developed its reflections on social practices and collective action. The working hypothesis that guides this analysis estimates that in these reflections a problematic relationship between subject and society is verified, which connects the discipline with an unresolved obstacle within psychology and social theory, and cannot, therefore, leave the representations of the subject of the conscience and the will as expressions of the psychological individual. In open counterpoint, the article proposes to introduce conceptual operations that allow us to open this problem with a view to thinking about other modes of agency, irreducible to the individual. The theory of performativity, as well as contemporary developments on the power and politics of life, would enable a reflection on the conformation of subjects in interstitial spaces between desire and the agonistic dispositions of the collective, between the inside and the outside, that is, in the midst of power relations, thus highlighting the creative and liminal dimension of the processes of subjectivation, as well as its profound ethical dimension. This last aspect will allow us to notice the constitutive exposition or opening in which all subjectivity is produced, as well as the conflicting and ambivalent dimension in which it takes place, when debating modulations of support and resistance. Finally, the article highlights the performative dimension as a fundamental element of these processes, as it consists of the affirmative act of the collective transformation processes that involve subjects in the extensive dimension of their vital modulations. © The Editor(s) (if applicable) and The Author(s), under exclusive licence to Springer Nature Switzerland AG 2021.